The legal regime applicable to illicit profitable acts: between Tort Law and Unjust Enrichment - Alciati Valim, Thalles Ricardo (2024)
This paper aims to identify the appropriate conceptual framework for illicit profitable acts, understood as those from which the wrongdoer derives advantages that exceed the mere dimension of the obligation to compensate. To do so, the fields of Tort Law and Unjust Enrichment are studied, both of which are considered candidates for legal application. It becomes evident that Tort Law’s structure is inadequate for the pursued task, as the purpose of compensation is different: it serves to repair damage. On the other hand, recognizing partial forms of unjust enrichment (especially enrichment through intervention) may serve to require the wrongdoer to restitute the economic benefits obtained due to reprehensible conduct.